Answer:
34
Step-by-step explanation:
x=3+√8
y =3-√8
now,
1/x^2+1/y^2
=1/(3+√8)² + 1/(3-√8)²
= [(3-√8)²+(3+√8)²] / (3+√8)²(3-√8)² [L.C.M = (3+√8)²(3-√8)² ]
=[(3-√8+3+√8)²-2(3-√8)(3+√8) ] / [(3+√8)(3-√8)]²
=[6²-2.(3²-√8² )] / (3²-√8²)² [ a²+ b²=(a+b)²-2ab]
=[36-2(9-8) ]/ (9-8)²
=[36-2.1] / 1²
=34
Answer:
No Solution
Explanation:
5(3 - 9b) = 3(-15b – 2)
Expand
5(3 - 9b): 15 - 45b
3(-15b - 2): -45b - 6
15 - 45b = -45b - 6
Subtract 5 From Both Sides
15 - 45b - 15 = -45b - 6 - 15
Simplify
-45b = -45b - 21
Add 15b To Both Sides
-45b + 15b = -45b - 21 + 15b
Simplify
0 = -21
No Solution
Answer:
1. 6
2. 24
Step-by-step explanation:
Substitute in the values for <em>t</em> and solve the expression.
WE KNOW THAT THE VOLUME OF THE CUBE IS '
V=a^3
our a=7
V=343 cm^3